Indian Journal of Nematology 4(2): 1974 (Indian Journal of Nematology, 2024)
EDITORIAL BOARDS. K. PRASAD                   - Chief EditorABRAR M. KHAN             - MemberS. KHERA                          - MemberK. C. SANWAL                 - MemberD. R. DASGUPTA            - Assistant Editor